Food Origin Fibrinolytic Enzyme With Multiple Actions - Laurentia Stephani; Raymond Rubianto Tjandrawinata; Diana Nur Afifah; Yanti Lim; Wangsa Tirta Ismaya; Maggy Thenawidjaja Suhartono (Bogor Agricultural University, Indonesia, 2017)
Many health related problems such as cardiovascular diseases are associated with the formation of excessive clot in the blood (thrombus). Approaches in cardiovascular disease treatment are preventing the formation or removing the thrombus. The present thrombolytic agents can be classified as plasminogen activators, fibrinolytic enzyme which directly degrades fibrinogen or fibrin and heparin type which act as thrombin inhibitor. Recently, microbial fibrinolytic enzymes of food origin receive more attention that leads to escalating efforts to explore traditional fermented foods as the natural sources. We have successfully isolated microorganism from Indonesian fermented soybean tofu dregs “Oncom” that secretes fibrinolytic enzyme. The microorganism identified as Stenotrophomonas sp. is unique because most of the reported fibrinolytic microorganism belongs to Bacillus sp. This isolate was found to produce extracellular fibrinolytic enzyme which could degrade fibrinogen and fibrin directly as determined by fibrinogen zymography and fibrin plate methods. More importantly, the 30-kD purified enzymes was found to demonstrate not only fibrin and fibrinogen degradation capabilities, but also acted as thrombin inhibitor as determined using specific substrates for thrombin. This is the first report of a fibrinolytic enzyme that demonstrates additional synergistic activities. This finding accentuates the importance of further development of the enzyme into a powerful agent to treat the thrombus-related disease effectively.